TRAINING ON MAKING FUND PROPOSALS FROM GOVERNMENT AND PRIVATE INSTITUTIONS FOR MSME ACTORS - Misrita Misrita; Yetrie Ludang; Irma Suryani; Imam Qalyubi; Srie Rosmila Wati; Mita Sari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Talio Village is one of the villages in the Pulang Pisau Regency area which has several MSMEs as a group of small and medium enterprises at this village level. As a small and medium community business, of course, it requires the ability of its members to manage, create activities and develop themselves. One of the supporting capabilities in entrepreneurship is the strength of sufficient capital so that the business can develop. One effort that can be done to obtain capital is to seek assistance from the government and the private sector by submitting grant proposals. Making a proposal is one of the skills needed to advance the activities of MSME actors. By having the capability and ability to make proposals, it will be easy for MSME actors to seek financial assistance that can support MSME businesses. With this training activity, MSME actors can enrich their insights and abilities regarding making grant proposals from government and private institutions for MSME actors